Optimizing Recruitment Strategies and Physician Engagement for Stroke Recovery Research. Issue 1 (January 2021) - Morton, Allegra; Myers, Moira; Whitaker, Alicen A.; Kempf, Katie S.; Eickmeyer, Sarah M.; Abraham, Michael; Rippee, Michael A.; Billinger, Sandra A.
Abstract : Background and Purpose: A major challenge for stroke rehabilitation and recovery research is the recruitment and retention of participants. Our prior challenges and successes have influenced our team to rethink our approach and the potential for large-scale stroke recruitment. Summary of Key Points: In this special interest article, we highlight how the adoption and implementation of recruitment strategies such as physician engagement and a streamlined "customer service" approach helped us improve our enrollment and maximize efficiency. Another positive outcome of enrollment was increased representation of those who identify as underrepresented minority or live in rural areas. Recommendations for Clinical Practice: Rethinking our recruitment processes and infrastructure allowed for greater interprofessional interactions, minimal burden for our stroke physician team members, and maximized enrollment into our stroke studies. Video Abstract available for more insights from the authors (see the Video, Supplemental Digital Content 1, available at: http://links.lww.com/JNPT/A324 ). Abstract : Supplemental Digital Content is Available in the Text.